Preterm Births: A Global Health Problem. Issue 5 (September 2015) - Ryan, Jane Greene; Dogbey, Evelyn
Abstract : Abstract: Globally, in 2012, there were 15 million babies born preterm. The majority of preterm births occur in resource-poor countries including India, Nigeria, Pakistan, and the Democratic Republic of Congo where many die due to lack of basic skilled nursing care. In September 2000, the United Nations signed the Millennium Development Declaration establishing eight Millennium Development Goals (MDGs). These MDGs provide specific, measurable targets that are designed to provide equitable health to all, particularly the most vulnerable including preterm babies. On May 2, 2014, the World Health Organization specifically targeted the nursing workforce as a key stakeholder in strategies to reduce global prematurity and end preventable preterm newborn deaths. Specific strategies include primary care, screening for risk factors, kangaroo mother care, and early initiation of breastfeeding with exclusive breastfeeding for the first 6 months of life. By sharing our knowledge and skills, nurses can contribute to global actions being taken to end preventable preterm newborn deaths. Abstract : Preterm birth is a significant health issue facing millions of babies and their families each year. Babies born preterm in developing countries with few resources often have poor outcomes. The United Nations and the World Health Organization have specifically identified nurses and midwives as key stakeholders capable of implementing strategies to decrease the global impact of preterm births.